Implementasi Produk Pembiayaan di PT. Permodalan Nasional Madani (PNM) Mekaar Syariah Kuningan terhadap Peningkatan Ekonomi Nasabah - Muliasari, Chiska Alih; Wahyuni, Neneng (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2025)
Indonesia is a country rich in human resources in the current era of globalization, the business world is increasingly developing. PT. Permodalan Nasional Madani (PNM) Mekaar Syariah is a leading financial institution with BUMN status that specializes in women as its clients. The type of research that the author conducted was field research using qualitative methods by using primary data and secondary data. The results of PNM Mekaar's research are financial institutions that do not impose collateral or other guarantees on customers. PNM Mekaar is a pioneer of financial institutions that prioritize groups and use customers' attendance at weekly group meetings as collateral. Factors that can cause the customer's business to not develop are inaccuracies in providing financing products, customers who choose to stop their business because the business capital is not returned, the increasing number of competitors who are more competent in business so they prefer to close and too many loans which result in customers dig holes and cover holes, causing new problems for customers which result in customers having difficulty paying their installments.